Etiologic factors associated with anterior knee pain in distance runners - Duffey, M. J.; Martin, D. F.; Cannon, D. W.; Craven, T.; Messier, S. P. (Medicine & Science in Sports & Exercise, 2000)
PURPOSE: The objectives of this study were 1) to examine the differences between a noninjured (C) cohort of runners (N = 70) and runners afflicted with anterior knee pain (AKP) according to selected training, anthropometric, rearfoot motion, ground reaction force, and muscular strength and endurance variables; 2) to explore multivariate relationships among these measures in the well and injured groups; and 3) to develop specific hypotheses concerning risk factors for injury that will later be tested in a prospective clinical study. METHODS: High speed videography (200 frames x s(-1)), a force platform (500Hz), and a Cybex II+ isokinetic dynamometer were used to assess rearfoot motion, ground reaction forces, and knee muscular strength and endurance, respectively. A linear discriminant function was performed on each of the five categories of variables and revealed 19 significant (P < or = 0.05) predictors. These variables were then combined and a final discriminant function analysis was performed. RESULTS: Pronation through the first 10% of stance, arch index, shoe mileage, and extension peak torque were the best overall (P < or = 0.05) predictors. The AKP group had smaller mean values on all four significant predictors. CONCLUSION: With the exception of shoe mileage, which is likely a response to rather than a risk factor for AKP, these results should prove useful to clinicians in identifying runners at risk for anterior knee pain.